2016
DOI: 10.1016/j.bjid.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum CA 19-9 levels in patients with pulmonary nontuberculous mycobacterial disease

Abstract: Increased serum CA 19-9 levels in patients with nonmalignant diseases have been investigated in previous reports. This study evaluates the clinical significance of serum CA 19-9 elevation in pulmonary nontuberculous mycobacterial disease and pulmonary tuberculosis. The median CA 19-9 level was higher in patients with pulmonary nontuberculous mycobacterial disease than in patients with pulmonary tuberculosis (pulmonary nontuberculous mycobacterial disease: 13.80, tuberculosis: 5.85, p<0.001). A multivariate log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
(41 reference statements)
0
19
0
Order By: Relevance
“…Hong et al 13 examined the clinical significance of CA19-9 as a biomarker for monitoring treatment for NTM-PD. In that study, patients with good treatment response showed a significant decline in the CA19-9 level, while no difference was observed in the CA19-9 level between before and after treatment in non-responders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hong et al 13 examined the clinical significance of CA19-9 as a biomarker for monitoring treatment for NTM-PD. In that study, patients with good treatment response showed a significant decline in the CA19-9 level, while no difference was observed in the CA19-9 level between before and after treatment in non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is dire need for a simple biomarker that reflects the disease activity of NTM-PD. Few studies have reported on the hematological biomarkers of NTM-PD, including IgA antibodies against glycopeptidolipids (GPL) 11 , serum Krebs von den Lungen-6 (KL-6) 12 , and carbohydrate antigen 19-9 (CA19-9) 13,14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated blood levels of CA 19-9 are also seen in various forms of chronic lung disease, including bronchiectasis. Recently, CA 19-9 was examined as biomarker of treatment response among 24 patients with NTM lung disease in South Korea ( Hong et al, 2016 ). Among 17 patients with treatment response (defined as symptomatic improvement and sputum culture conversion within 12 months of therapy), CA 19-9 levels significant declined, while no difference was observed among the 7 patients without clinical response.…”
Section: Current Approaches To Monitoring Treatment Response To Ntm Dmentioning
confidence: 99%
“…In addition, for elderly patients infected with PNTM who need to be treated with macrolides, rifamycin and FQs, comorbidities and associated concomitant therapies should be determined since these drugs may interact with those that interact with P-450 and disturb the metabolism of drugs [367]. Hong et al (2015) suggested that serum carbohydrate antigen (CA) 19-9 can be a useful marker to monitor the therapeutic responses in PNTM as it is higher in PNTM than in TB, and its concentration is reduced after successful PNTM treatment but not in TB [368].…”
Section: (B) Treatmentmentioning
confidence: 99%